2019
DOI: 10.1136/bmjopen-2018-027402
|View full text |Cite|
|
Sign up to set email alerts
|

Strategies occupational therapists employ to facilitate work-related transitions for persons with hand injuries: a study protocol for a scoping review

Abstract: IntroductionHands make it possible to be employable and productive, to communicate non-verbally and to perform fine motor tasks required in day-to-day activities. Sustaining a hand injury can be detrimental to function including the ability to work. As the literature on work-related transitions is scattered across a range of journals, it is difficult to get a sense of how much literature there is, what is known and where the gaps lie. This scoping study will provide a single source of up-to-date evidence to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The primary reviewer will read each of the selected full-text publications. A data charting form, adapted from Uys et al 18 will be used in the extraction of the data that will answer the research questions and organise existing literature. To test the feasibility, the form will be tested by the lead reviewer on a random sample of the publications included in the review.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The primary reviewer will read each of the selected full-text publications. A data charting form, adapted from Uys et al 18 will be used in the extraction of the data that will answer the research questions and organise existing literature. To test the feasibility, the form will be tested by the lead reviewer on a random sample of the publications included in the review.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The methodology was informed by Arksey and O'Malley's (2005) framework and was structured according to five stages: (a) identifying the research question, (b) identifying relevant studies, (c) study selection, (d) charting the data and (e) collating, summarizing and reporting the results. A protocol was published to obtain expert feedback to guide the review process (Uys et al, 2019). This scoping review was conducted in accordance with the published study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The incongruency between education and practice was believed to often lead to a reality shock in the practice environment. (23)The sources reviewed suggested that new health professionals experienced high levels of tension, coupled with anxiety and nervousness upon entering the world of practice (6,7,20,(25)(26)(27)29,32,33). O'shea et al (22) emphasized that the 'reality shock' and anxiety among new health professionals was intense, particularly in the rst ve months of transition into practice.…”
Section: Theme 3: Professional Competencesmentioning
confidence: 99%
“…New health professionals often experienced con ict between their expectations of practice and the reality of practice (31). They experienced varying levels of stress beyond their expectations which impacted their transition (3,6,13,20,21,25,26,(30)(31)(32)(33). New health professionals often felt incapable of managing stressful emotional work-related situations such as death and dying (13,20,23).…”
Section: Theme 3: Professional Competencesmentioning
confidence: 99%